Contribution of Siderophore Systems to Growth and Urinary Tract Colonization of Asymptomatic Bacteriuria Escherichia coli - Watts, Rebecca E. (American Society for Microbiology, 2012)
The molecular mechanisms that define asymptomatic bacteriuria (ABU) Escherichia coli colonization of the human urinary tract remain to be properly elucidated. Here, we utilize ABU E. coli strain 83972 as a model to dissect the contribution of siderophores to iron acquisition, growth, fitness, and colonization of the urinary tract. We show that E. coli 83972 produces enterobactin, salmochelin, aerobactin, and yersiniabactin and examine the role of these systems using mutants defective in siderophore biosynthesis and uptake. Enterobactin and aerobactin contributed most to total siderophore activity and growth in defined iron-deficient medium. No siderophores were detected in an 83972 quadruple mutant deficient in all four siderophore biosynthesis pathways; this mutant did not grow in defined iron-deficient medium but grew in iron-limited pooled human urine due to iron uptake via the FecA ferric citrate receptor. In a mixed 1:1 growth assay with strain 83972, there was no fitness disadvantage of the 83972 quadruple biosynthetic mutant, demonstrating its capacity to act as a “cheater” and utilize siderophores produced by the wild-type strain for iron uptake. An 83972 enterobactin/salmochelin double receptor mutant was outcompeted by 83972 in human urine and the mouse urinary tract, indicating a role for catecholate receptors in urinary tract colonization.